2022
DOI: 10.1155/2022/9130400
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Commercial Feed with Fresh Black Soldier Fly (Hermetia illucens) Larvae in Pacific White Shrimp (Litopenaeus vannamei)

Abstract: This study evaluated survival, growth performance, digestive enzyme activities, intestinal histology, and antioxidant enzyme activities of the Pacific white shrimp (Litopenaeus vannamei), which were fed with five different diets, containing 0%, 25%, 50%, 75%, and 100% fresh black soldier fly larvae (BSFL), respectively, to replace commercial feed at an equal wet weight. The cultured experiment was lasted for 45 days, and the results showed that survival rate (SR), final body weight (FBW), and weight gain (WG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Cai et al (2022) found that replacing FM by MW decreased the growth performance of L. vannamei. These different results may be due to the differences in the species of aquatic animals, their life stage, the type of insects and the breeding substrate of the insects, as well as the way the diet is processed (He et al, 2022;Tschirner and Simon, 2015). As in the present study, the replacement of FM by MW did not affect the growth performance of juvenile white shrimp.…”
Section: Growth Performancecontrasting
confidence: 57%
“…Cai et al (2022) found that replacing FM by MW decreased the growth performance of L. vannamei. These different results may be due to the differences in the species of aquatic animals, their life stage, the type of insects and the breeding substrate of the insects, as well as the way the diet is processed (He et al, 2022;Tschirner and Simon, 2015). As in the present study, the replacement of FM by MW did not affect the growth performance of juvenile white shrimp.…”
Section: Growth Performancecontrasting
confidence: 57%
“…However, fresh insects also have their advantages, such as simple feeding, low nutrient losses, and easier nutrition enhancement. A recent study by our team showed no significant negative effects on shrimp growth when up to 50% of the commercial feed was replaced by fresh BSFL (He et al, 2022). Aquaculture outcome is not defined solely by growth performance, but issues concerning aquatic animals' welfare also need to be taken into accounts, such as the water quality of the aquaculture environment and the immune capacity of different tissues.…”
Section: Introductionmentioning
confidence: 95%
“…Incorporating insects into compound aquafeeds is Cummins et al, 2017;Mazlum et al, 2021;Motte et al, 2019;Panini et al, 2017a,b;Peh et al, 2021;Rahimnejad et al, 2019;Richardson et al, a novel approach even though insects are part of the natural diet of many fish (Howe et al, 2014;Whitley and Bollens, 2014) and crustaceans (Muangyao et al, 2019). Insect supplements improve growth, gut health and immunity, although a high content of insect meal can be detrimental (Table S1) (Cummins et al, 2017;He et al, 2022;Wang et al, 2021. Specific effects depend on the processing method, feed composition and insect/crustacean species.…”
Section: Insect-based Crustacean Feedmentioning
confidence: 99%
“…In this species, fishmeal can be fully replaced with T. molitor meal without detrimental effects, whereas high proportions of H. illucens, M. domestica or the Domestic silk moth (Bombyx mori) can hamper growth and affect health (Chen et al, 2021a;Choi et al, 2018;Cummins et al, 2017;De León-Ramírez et al, 2018;Huang et al, 2020;Rahimnejad et al, 2019;Wang et al, 2021). For example, insect meal can affect the fatty acid composition of crustaceans (Shin and Lee, 2021), and a high proportion of insect meal can lead to hepatopancreatic damage in shrimps, potentially driven by the high lipid content and particularly by monounsaturated and saturated fatty acids (Chen et al, 2021a,b;Cummins et al, 2017;He et al, 2022;Wang et al, 2021). Defatted H. illucens meal was able to replace 60% of the fishmeal without negative effects in L. vannamei compared to <30% for full-fat insect meal (Chen et al, 2021a;Hu et al, 2019b;Wang et al, 2021).…”
Section: Insect-based Crustacean Feedmentioning
confidence: 99%